Analisis gaya mengajar guru Bahasa Inggris di kelas XI SMK N 1 Bangli - Ni Luh Eka Andriani; Luh Made Dwi Wedayanthi; Kadek Dwi Pebriyanti (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research is motivated by the need to understand the variations in teaching styles among English teachers at the high school level, particularly at SMK N 1 Bangli, with a focus on classical, technological, personalized, and interactional dimensions. The objective of the study is to identify and analyze the teaching styles applied by 11th-grade English teachers and evaluate their impact on the learning process. Through direct observation and curriculum document analysis, the findings reveal a diversity of teaching styles, including the use of a combination of classical, technological, and personalized styles. Technological facility constraints remain a challenge, but teachers still play a key role in guiding learning. Personalized teaching styles show efforts to address individual student needs, while interactional teaching styles enhance active student participation. The implications of this research include the need for more attention to the development of learning technology facilities and strengthening the implementation of personalized teaching styles to improve the quality of high school learning. These findings provide valuable insights for educational policy development and teacher professional development, with a focus on enhancing the quality and relevance of learning in the secondary education environment.